Predictors of early return to sport after surgical repair of proximal hamstring complex injuries in professional athletes: A prospective study - Lefèvre, N.; Moussa, M. K.; Valentin, E.; Meyer, A.; Bohu, Y.; Gerometta, A.; Khiami, F.; Grimaud, O.; Khalaf, Z.; Hardy, A. (The American Journal of Sports Medicine, 2024)
Background: Proximal hamstring complex injury (PHCI) is a common injury among professional athletes, particularly those participating in pivot contact sports. Previous studies have suggested that surgery can be effective in restoring function and allowing athletes to return to sport (RTS), but the factors influencing successful RTS have been less clear.